Behaviour of hydrogenated lead–lithium alloy. (12th January 2017) - Pozio, A.; Carewska, M.; Santucci, A.; Tosti, S.
Abstract: Eutectic Pb–Li (lithium 15.6 at.%) alloy has been tested by means of thermogravimetric analysis under different hydrogenation conditions in the temperature range 25–650 °C. The melting temperature of the material changes irreversibly after the first heating ramp, from that of the eutectic alloy (240 °C) to that of pure lead (330 °C). The capacity to upload hydrogen depends on the thermal cycling and on the humidity presence. Particularly, it has observed that the presence of water traces in the environment leads to the formation of lithium hydroxide. This reaction affects dramatically the hydrogen uploading of the Pb–Li. Such a behavior is discussed in details by considering the change of weight of the Pb–Li along hydrogenation and thermal cycling. Highlights: The hydrogen uploading in the Pb–Li eutectic alloy has been measured via gravimetric methods. The tests demonstrated the formation of LiOH due to the presence of humidity. The formation of LiOH affected strongly the hydrogen uploading. The control of humidity in liquid breeders is of main importance for controlling the tritium inventory.